Sulfur partitioning between aqueous fluids and felsic melts at high pressures: Implications for sulfur migration in subduction zones - Lanqin Li; Xingcheng Liu; Ting Xu; Xiaolin Xiong; Jintuan Wang; Li Li (Scientific Reports)
Abstract Sulfur (S), an essential volatile in subduction zone magmatism, exhibits higher solubility in aqueous fluids compared to silicate melts. Despite its importance, the partitioning of S between aqueous fluids and silicate melts under the conditions of subduction zone, critical for magma generation and evolution, remains poorly understood. To address this knowledge gap, we performed piston-cylinder experiments at a temperature of 950 ℃ and pressures of 1 and 2 GPa, investigating the effects of various parameters including oxygen fugacity, melt composition, fluid composition (salinity) and pressure on S partitioning between aqueous fluid and silicate melt (DS fluid/melt). Our results indicate that the DS fluid/melt is always large (> > 1), and S prefers to enter the aqueous fluid at high pressures. However, the DS fluid/melt decreases with increasing pressure from 1 to 2 GPa. Specifically, under reducing conditions (Ni-NiO buffer), DS fluid/melt decreased from 147 ± 40 to 20 ± 2, whereas under moderately oxidizing conditions (Re-ReO2 buffer), it decreased from 27 ± 1 to 20 ± 2. These results stress the strong affinity of S for aqueous fluids at high pressures. Together with the great capacity for S dissolution in the H2O-rich magma within the deep Earth, fluid-saturated felsic magma efficiently transports substantial amounts of S from deep to shallow regions in subduction zone settings. This process plays a crucial role in the formation of giant porphyry deposits and provides a potential source of excess S released during explosive volcanic eruptions.